A Rare Case of Ovarian Serous Borderline Tumor with Brain Metastasis. (22nd May 2019) - Veran-Taguibao, Sonia; Taguibao, Roberto Alvaro A.; Gallegos, Nicolas; Farzaneh, Ted; Kim, Ronald; Lin, Fritz; Lu, Di
Abstract : Background . Serous borderline tumor represents a group of noninvasive tumor of the ovary bridging between benign serous cystadenoma and serous carcinoma. They are commonly seen in younger women and usually have an excellent outcome but seldom show local recurrence (J. F. Leake et al. 1991). Metastasis to the lymph nodes has rarely been reported (M. D. Chamberlin et al., 2001; M. B. Verbruggen et al., 2006). Moreover, the brain is exceptionally a rare metastatic site for ovarian tumor. There is one case of an advanced staged SBT with micropapillary pattern metastasis to the brain recently and by far it is the most distant metastasis reported (M. D. Martin et al., 2017). However, to the best of our knowledge, no report has been documented for a recurrent stage 1 typical SBT metastasizing to the brain.